2011 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2011
DOI: 10.1109/icassp.2011.5946987
|View full text |Cite
|
Sign up to set email alerts
|

RSS-based sensor localization with unknown transmit power

Abstract: Received signal strength (RSS)-based single source localization when there is not a prior knowledge about the transmit power of the source is investigated. Because of nonconvex behavior of maximum likelihood (ML) estimator, convoluted computations are required to achieve its global minimum. Therefore, we propose a novel semidefinite programming (SDP) approach by approximating ML problem to a convex optimization problem which can be solved very efficiently. Computer simulations show that our proposed SDP has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 11 publications
0
48
0
Order By: Relevance
“…2) P T is not known: The worst case complexity of "SOCP3" approach is O(N 3.5 ), while the complexity of [4] and [5] is O(N 3.5 ) and O(N ), and we call them here "SDP" and "WANG", respectively.…”
Section: Complexity Analysis 1) P T Is Knownmentioning
confidence: 99%
See 2 more Smart Citations
“…2) P T is not known: The worst case complexity of "SOCP3" approach is O(N 3.5 ), while the complexity of [4] and [5] is O(N 3.5 ) and O(N ), and we call them here "SDP" and "WANG", respectively.…”
Section: Complexity Analysis 1) P T Is Knownmentioning
confidence: 99%
“…3 depicts the RMSEs versus different N . The red solid line with "⊲" denotes the performance of "SOCP3", while the black solid line and the blue dashed line with "⊲" represent the performances of [5] and [4], called here "WANG" and "SDP", respectively. As before, the black dotted line plots the unbiased CRB.…”
Section: A P T Knownmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that replacing the ℓ2 norm with the ℓ1 norm for solving optimization problems can also be found in other work, e.g., in [24]. By introducing di = ∥x − si∥ 2 > 0 and the slack variable ti ≥ 0, we can convert the optimization problem (7) into…”
Section: Rss-based Approachmentioning
confidence: 99%
“…The ML estimator of RSS localization was derived in [3]. It can be shown that the cost function of the ML estimator is highly nonlinear and nonconvex [8,9]. The ML estimator does not have a closed-form solution, but it can be approximately solved by iterative algorithms [10,11].…”
Section: Introductionmentioning
confidence: 99%